A Twitter Sentiment Analysis on Circular Economy - Maulida, Syahdatul (Business and Sustainability, 2022)
This research aims to understand the development of public sentiment towards the circular economy. The research adopts a qualitative method with a focus on sentiment analysis using primary data obtained from Twitter. The tweet data is then processed using the VADER Python programming. The results show significant daily fluctuations in the number of tweets discussing the circular economy. The peak tweet activity occurs around the middle of the month, reaching a maximum of 970 tweets. London, England, is noted as the location with the highest tweet activity related to the circular economy, reaching a total of 666 tweets. In terms of sentiment, the majority of tweets exhibit a positive attitude with a percentage of 64.5%. This positive sentiment reflects optimism and support for the concept of the circular economy. The successful implementation of the circular economy paradigm is proven to develop sustainable business and development models, creating hope for a new supportive ecosystem, where economic, environmental, and social sectors are integrated.